2022
DOI: 10.3390/genes13101869
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology in Amerindians of the Brazilian Amazon Reveals New Genetic Variants in DNA Repair Genes

Abstract: Native American populations from the Brazilian Amazon have a low genetic diversity and a different genetic profile when compared to people from other continents. Despite this, few studies have been conducted in this group, and there is no description of their genetic data in the various currently existent international databases. The characterization of the genomic profile of a population not only has an impact in studies of population genetics, but also helps to advance diagnostic and therapeutic response stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(61 reference statements)
1
1
0
Order By: Relevance
“…Thus, the correlation of Amerindian ancestry with the severe toxicities observed may potentially result from specific gene variants within this ethnic group found in mixed populations. Other studies investigating the exomes of indigenous people have already demonstrated the existence of novel variants in other genes important for pharmacogenetics, which further supports our hypothesis [29][30][31].…”
Section: Discussionsupporting
confidence: 89%
“…Thus, the correlation of Amerindian ancestry with the severe toxicities observed may potentially result from specific gene variants within this ethnic group found in mixed populations. Other studies investigating the exomes of indigenous people have already demonstrated the existence of novel variants in other genes important for pharmacogenetics, which further supports our hypothesis [29][30][31].…”
Section: Discussionsupporting
confidence: 89%
“…Despite being a highly type of neoplastic study, only rare studies have been conducted in populations genetically heterogeneous or in original people, and an even smaller portion of the Brazilian indigenous population [ 8 ]. In this way, it is extremely valid to analyze the genetic profile of this original population of the Brazilian Amazon, in order to investigate genetic variants already elucidated in the world literature, as well as unknown or unscreened variants that may be associated with the development of Gastric Cancer.…”
Section: Introductionmentioning
confidence: 99%